1996
DOI: 10.1056/nejm199606063342302
|View full text |Cite
|
Sign up to set email alerts
|

Oral Ganciclovir for the Prevention of Cytomegalovirus Disease in Persons with AIDS

Abstract: In persons with advanced AIDS, phophylactic oral ganciclovir significantly reduces the risk of CMV disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
94
2
5

Year Published

1997
1997
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 288 publications
(104 citation statements)
references
References 32 publications
3
94
2
5
Order By: Relevance
“…First, exposure to this virus is almost universal in the HIVϩ population (18), and it thus serves as a good general model of an Ag-specific response. Second, CMV also happens to be the most common cause of life-threatening viral infection in AIDS (affecting up to 40% of such patients with either retinitis or other tissue manifestations; 17,18), and delineation of the fate of CMV responsive T cells might lead to a better understanding of the factors responsible for the onset of opportunistic infection.…”
Section: Discussionmentioning
confidence: 99%
“…First, exposure to this virus is almost universal in the HIVϩ population (18), and it thus serves as a good general model of an Ag-specific response. Second, CMV also happens to be the most common cause of life-threatening viral infection in AIDS (affecting up to 40% of such patients with either retinitis or other tissue manifestations; 17,18), and delineation of the fate of CMV responsive T cells might lead to a better understanding of the factors responsible for the onset of opportunistic infection.…”
Section: Discussionmentioning
confidence: 99%
“…Randomized placebo-controlled studies of oral ganciclovir for primary prophylaxis have demonstrated a reduction in the incidence of retinal and gastrointestinal involvement. In one study, 80 the incidence of CMV disease at 1 year was 14% in the treated group compared to 26% in the placebo group. The number of patients developing gastrointestinal CMV was low in both groups.…”
Section: Cytomegalovirusmentioning
confidence: 96%
“…These lesions can present at the time of seroconversion, 170 although typically occur when immunode®ciency is severe; the median CD4 count in these patients is <50/mm 3 . 80 Several studies have identi®ed HIV-infected in¯ammatory cells in the ulcer base of these lesions, suggesting an aetiological role for HIV. 171,172 However, HIV has not been identi®ed in oesophageal squamous mucosa but rather in in¯am-matory cells, and has been found in HIV-infected patients with oesophageal diseases other than IEU.…”
Section: Idiopathic Oesophageal Ulcermentioning
confidence: 99%
“…[11] Early detection is very important in treating opportunistic infections and there are many drugs to improve the survival of such patients. [12] …”
Section: Detection Of Opportunistic Dna Viral Infections By Multiplexmentioning
confidence: 99%